Examining the relationship between safety culture maturity and safety performance of the mining industry. (March 2019) - Stemn, Eric; Bofinger, Carmel; Cliff, David; Hassall, Maureen E.
Highlights: This paper examined the relationship between safety culture and incidence rate of mines. The safety culture maturity of the mines was determined through self-reported rating. The mines had statistically significant differences in their mean incidence rate and safety culture maturity scores. The safety culture maturity and incidence rate of the mines were significantly correlated. Abstract: A mature safety culture is regarded as an important means of ensuring good safety performance, particularly in reducing accidents. However, there is little empirical evidence in the literature that links safety culture maturity with actual safety performance metric. In this study, a safety culture maturity framework was used to examine the safety culture maturity level of mines in Ghana, and to explore the relationship of cultural maturity with accident rates. The safety culture maturity framework used consisted of 3 person and 10 system elements across five levels of culture maturity. A survey comprising the 13 elements was conducted among 828 employees of four large-scale gold mines in Ghana. Through principal component analysis, the structure of the framework was found valid and produced a good fit after testing the model through confirmatory factor analysis. One-way ANOVA showed that the mines had statistically significant differences in their mean incidence rate and pairwise comparison test revealed specific statistically significant mines. Similarly, Kruskal-Wallis H test also showed that the mines' safety culture maturity scores differed significantly from each other and a pairwise test identified specific mines with significant differences. It was found that mines with lower incidence rates consistently had higher safety culture maturity scores for the elements than mines with higher incidence rate. Also, correlation analysis indicated a strong negative correlation between the incidence rate and most elements of the safety culture maturity framework. The model/framework used was found useful and practical to both employees and management, enabling the identification of weak areas that require improvements interventions.